2021
DOI: 10.1073/pnas.2024912118
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment modeling reveals near-channel management as cost-effective to improve water quality in agricultural watersheds

Abstract: Despite decades of policy that strives to reduce nutrient and sediment export from agricultural fields, surface water quality in intensively managed agricultural landscapes remains highly degraded. Recent analyses show that current conservation efforts are not sufficient to reverse widespread water degradation in Midwestern agricultural systems. Intensifying row crop agriculture and increasing climate pressure require a more integrated approach to water quality management that addresses diverse sources of nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 59 publications
1
18
1
Order By: Relevance
“…Of all nitrate exported from soil in our study, the highest fraction intercepted by restored wetlands was 16% for full adoption of the WRP (Figure 3). In contrast, our analysis of FWP and WRP restoration predicts greater nitrate removal from wetland restoration than integrated assessment modeling (<2%) 8,11 , or biophysical modeling (12%) 19 when wetland restoration occurs only on non-tile-drained land. The wide range in previous estimates for the efficacy of interventions reflect the importance of comprehensively accounting for the entire watershed system in estimating restoration outcomes, not just isolated components.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…Of all nitrate exported from soil in our study, the highest fraction intercepted by restored wetlands was 16% for full adoption of the WRP (Figure 3). In contrast, our analysis of FWP and WRP restoration predicts greater nitrate removal from wetland restoration than integrated assessment modeling (<2%) 8,11 , or biophysical modeling (12%) 19 when wetland restoration occurs only on non-tile-drained land. The wide range in previous estimates for the efficacy of interventions reflect the importance of comprehensively accounting for the entire watershed system in estimating restoration outcomes, not just isolated components.…”
contrasting
confidence: 62%
“…Restored fluvial wetlands that exchange with river flows during downstream transport, and potentially intercept groundwater and river flux from all upstream croplands may be more effective at removing nitrogen than cropmargin wetlands at watershed scales 11…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the landscapescale, N retention potential of wetlandscapes can be quantified as a function of N retention in individual wetlands, as well as the distribution and connectivity of wetlands across the landscape. Hansen et al used a coupled model to explore N retention dynamics in the Le Sueur River Basin in the Minnesota River basin, and found restoration of floodplain wetlands to be the most cost-effective strategy for N retention [17]. Evenson et al found that restoring 2% of the area of the Upper Mississippi River Basin to wetlands can reduce the outlet N loads by 12% [18].…”
Section: Introductionmentioning
confidence: 99%
“…The case of wetlands deserves some additional attention as recent work has shown that fluvial wetlands, which are connected to rivers and streams, are particularly effective in removing legacy nitrogen too. Hansen et al (2021) apply an integrated assessment model to optimize nutrient policy in the Le Sueur River Basin (LSRB) of the Upper Mississippi and conclude that shallow fluvial wetlands are the most cost effective approach for reducing nitrate and sediment loads. The annualized installation and management costs are about $600 per acre per year (/a/y).…”
Section: Mitigating Nitrogen Pollutionmentioning
confidence: 99%